The Genetic Basis of Natural Variation in Oenological Traits in Saccharomyces Cerevisiae - Martinez-Fernandez, C; Ganga-Munoz, M; Garcia-Mena, V; Salinas-Sanhueza, F; Soto-Madrid, D (2012)
Sin Editorial Disponible